Toward a perspective of cultural friction in international business - Luo, Yadong; Shenkar, O. (2011)
This article introduces a new lens that addresses cultural interaction in global business. Shifting away from viewing culture in terms of its differences, the cultural friction lens captures the nature and magnitude of interaction between the cultural systems engaged in cross-border businesses. In this study we present that (1) cultural distance may not transform into a clash, or yield any meaningful interaction effect, negative or positive, until organizations truly engage in interactions; (2) cultural friction is situation-specific, subject to the influence of "drag" parameters, such as entry mode (e.g., contract vs. equity; greenfield vs. acquisition), workflow interdependence, breath of local stakeholders, speed and stage of international expansion, and depth of localization; and (3) cultural friction can be curtailed through a series of managerial mechanisms, or lubricants, around the points of cross-border contact. We also develop a measure of cultural friction and assess the implications for extant theories as well as for future theory development in international business.